Understanding L2 Demotivation Among Chinese Tertiary EFL Learners From an Activity Theory Perspective - Li, Chili (Frontiers in Psychology, 2021)
This study reports on the qualitative results of a large-scale study on second language (L2) demotivation among 14 Chinese EFL learners from an Activity Theory perspective. Data were collected from a semi-structured interview and analyzed by means of a qualitative content analysis approach. The results indicate that L2 demotivation prevailed among the participants. Their demotivation was caused by the contradiction within the activity system and influenced by a number of mediational factors including subject-mediated, rule-mediated, community-mediated, tool-mediated, and labor-of-division-mediated factors. The findings imply that L2 demotivation is a socially mediational construct and results from the interplay between agency and contextual realities in the activity system. The findings shed light on the formulating mechanism of L2 demotivation and provide insightful implications for overcoming the detrimental effect of demotivation in the Chinese EFL context and beyond.